2015
DOI: 10.1111/jog.12867
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the codon 72 polymorphism of the TP53 gene and the risk of recurrent implantation failure

Abstract: This meta-analysis shows that the TP53 codon 72 polymorphism is not associated with RIF risk in the overall population; however, associations were found in the Latin American population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…1,2 Recurrent implantation failure (RIF) is one of the most common causes of pregnancy failure after receiving ART. 3 The RIF is diagnosed when clinical pregnancy failure occurs after 2 consecutive IVF-ETs to the endometrium using at least 4 high-quality embryos. 4,5 Consequently, many patients with RIF have financial burden, physical and psychological stress, deterioration in the quality of life, and reduced marital and sexual satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recurrent implantation failure (RIF) is one of the most common causes of pregnancy failure after receiving ART. 3 The RIF is diagnosed when clinical pregnancy failure occurs after 2 consecutive IVF-ETs to the endometrium using at least 4 high-quality embryos. 4,5 Consequently, many patients with RIF have financial burden, physical and psychological stress, deterioration in the quality of life, and reduced marital and sexual satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…including tumor protein P53, cyclooxygenase-2 (COX-2), methylenetetrahydrofolate reductase (MTHFR), thymidylate synthase (TS), nuclear factor kappa B (NF-κB), plasminogen activator inhibitor-1, vascular endothelial growth factor, and leukocyte antigen-G [3][4][5][6][7][8][9]. Among these candidate RIFsusceptibility genes, the human leucocyte antigen-G (HLA-G) gene was one of the most extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…There are two meta-analyses examining the relationship between RIF and p53 p.Arg72Pro variant. Feng et al, 2016 found there was no significant association between RIF amongst patients with Pro/Pro genotype or Arg/Pro genotype compared to Arg/Arg [41], and similarly, Wiwanitkit et al, 2011 found there was no correlation between RIF and p53 variant [40]. Our study combining the genotype frequency data suggests that the frequency of Arg/Pro genotype carriers compared to Arg/Arg and Pro/Pro may be higher in the recurrent implantation failure population compared to the control group, which has not been shown in the previous meta-analyses.…”
Section: Discussionmentioning
confidence: 99%